2018
DOI: 10.1111/jgs.15419
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Medication‐Related Harm in Older Adults After Hospital Discharge: A Systematic Review

Abstract: MRH is common after hospital discharge in older adults, but methodological inconsistencies between studies and a paucity of data on risk factors limits clear understanding of the epidemiology. There is a need for international consensus on conducting and reporting MRH studies. Data from large, multicenter studies examining a range of biopsychosocial risk factors could provide insight into this important area of safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
95
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 51 publications
0
95
0
Order By: Relevance
“…In contrast, our collective understanding from available studies investigating the burden of MEs and ADEs in the period following hospital discharge to the community is limited, owing in part to there being no up-to-date published systematic reviews on this topic across all patient groups. One previous systematic review of drug-related problems occurring post-hospital discharge in elderly populations was published almost 10 years ago [20] and another from 2018 focused on medication-related harm also in elderly populations [21]. Given the level of interest in this stage of the patient journey amongst health leaders [22] and as new studies emerge in the field [23,24], there is a need to identify and collectively appraise global evidence on the burden and nature of MEs/ADEs post-hospital discharge across populations to best inform the development of remedial interventions and advance the WHO patient safety agenda.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, our collective understanding from available studies investigating the burden of MEs and ADEs in the period following hospital discharge to the community is limited, owing in part to there being no up-to-date published systematic reviews on this topic across all patient groups. One previous systematic review of drug-related problems occurring post-hospital discharge in elderly populations was published almost 10 years ago [20] and another from 2018 focused on medication-related harm also in elderly populations [21]. Given the level of interest in this stage of the patient journey amongst health leaders [22] and as new studies emerge in the field [23,24], there is a need to identify and collectively appraise global evidence on the burden and nature of MEs/ADEs post-hospital discharge across populations to best inform the development of remedial interventions and advance the WHO patient safety agenda.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults are at high risk of MRH due to their multimorbidity, polypharmacy, and age‐related changes in pharmacokinetics and pharmacodynamics . A recent systematic review of MRH in older adults found that between 17% to 51% of older adults experience MRH within 30 days of hospital discharge . In England, MRH is leading to an increasing number of hospital admissions .…”
Section: Introductionmentioning
confidence: 99%
“…2 A recent systematic review of MRH in older adults found that between 17% to 51% of older adults experience MRH within 30 days of hospital discharge. 3 In England, MRH is leading to an increasing number of hospital admissions. 4 The direct health care costs of MRH in older adults following hospital discharge in England is conservatively estimated at £400 million annually, of which 90% of cost is attributable to hospital readmission.…”
Section: Introductionmentioning
confidence: 99%
“…Anticoagulants are essential for the prevention and treatment of thromboembolic disorders but are also leading causes of medication‐related harm, including emergency department (ED) visits and hospital admissions for adverse drug events (ADEs) among older Americans . Administrative claims data are becoming increasingly utilized in postmarketing surveillance of drug safety .…”
Section: Introductionmentioning
confidence: 99%
“…Anticoagulants are essential for the prevention and treatment of thromboembolic disorders but are also leading causes of medication-related harm, including emergency department (ED) visits and hospital admissions for adverse drug events (ADEs) among older Americans. [1][2][3][4][5][6] Administrative claims data are becoming increasingly utilized in postmarketing surveillance of drug safety. 7 With five additional oral anticoagulants, other than warfarin, approved in the United States since 2010, 8 new anticoagulant management metrics in physician payment models, 9 and a focus on anticoagulants in Centers for Medicare & Medicaid Services (CMS) nationwide quality improvement initiatives, 10,11 administrative claims data will be increasingly important for assessing anticoagulant safety.…”
Section: Introductionmentioning
confidence: 99%